Temporal Analysis of Onion Prices in major Markets in India - Rajalaxmi, Amand; Gummagolmath, K.C. (Journal of Agricultural Extension Management, 2019)
In the last two decades, area and production of onion has increased,extendinginto non-traditional areas.However, there is a marginal increase in productivity.Price analysis of onion revealed that instability of the prices are high in domesticmarkets as observed in the last two decades period. On the contrary, in a fewmarkets, a positive correlation between arrivals and prices of onion is witnessedindicating the existence of exogenous factors such as more number of tradersoperating during harvesting season for hoarding of the stock for onward sale inother markets. Price analysis of onion also revealed that there is a cyclic trendof sudden hike in the price of onion. Thus there is a need to curb the exorbitantprice rise of onions by intervention of the government based on supply demanddynamics. There is also a need for strengthening the marketing information system and increasing of post-harvest management infrastructure for onion to resolve the issues related to onion supply chain in India, being the world’s second largest producer of onion.